Factors Influencing the Perception of Destination Brand Luxuriousness - Zoran Krupka; Andreja Dobra; Goran Vlašić (Naše gospodarstvo/Our economy, 2021)
The main purpose of this paper is to identify and investigate the factors that influence the building and managing of luxury destination brands. Based on a review of existing literature, the authors identified eight crucial factors: accommodation quality, quality of gastronomy offers, premium price, service quality, luxury shopping, unique experience, transportation infrastructure, and celebrity. The research was conducted on a sample of 619 respondents from 16 countries. Factor and regression analyses were used. The results indicate that the availability of celebrity and luxury shopping has the strongest significant influence on luxury destination brand building, while the impact of accommodation quality and a premium price is non-significant, and, interestingly, transportation infrastructure has a negative and significant impact. A convenience sample and the possibility of omitting certain factors (e.g. safety) from the research represent the main research limitations. This research contributes to marketing and brand management literature by identifying and investigating the factors that help in building and managing a luxury destination brand, which to date has been neglected in literature.